A Construal-Based Approach to Arabic Tenses - Khalid Saleh , Mustafa; Hasan Fatah, Azad (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
The present study aims to provide a cognitive account of tenses in Arabic. To do so, it employs perspective, a dimension of construal as proposed by Langacker’s construal theory (1987, 1991, 2008, 2013). What motivates the study is the presence of certain complex issues in Arabic tenses. One issue concerns the difference in between perfect and imperfect. The difficulty resides in that this operates on three levels, where one level may become more prominent, overshadowing or essentially eliminating the others. The perfect denotes past time, while the imperfect denotes present or future time. The imperfect denotes habitual or repeated action, or to one encapsulated as covering a space of time. The perfect denotes a fact, while the imperfect denotes a conceptual idea not necessarily realised. To study tense requires the study of aspect due to the fact the Arabic is an aspectual language. Therefore, it is hypothesized that both tense and aspect in Arabic are two sides of the same coin, i.e., they are inseparable.